Art that explores history: reconceptualizing contemporary art's historicity in the global framework [Rezension von: Art, history, and anachronic interventions since 1990 / Eva Kernbauer. - New York ; London : Routledge, Taylor & Francis Group, 2022] - Hopfener, Birgit (2022)
Eva Kernbauer’s book Art, History, and Anachronic Interventions Since 1990 argues that contemporary artistic historiographies can potentially help us to reconceptualize historiography and to rethink contemporary art’s historicity. Based on thorough analyses of historical and contemporary discourses of how art has been understood as contributing to historiography and philosophies of history, her analyses of artistic historiographies are not only about uncovering previously unknown histories and archives, but about theoretical reflections on history, history writing and time. This review summarizes Kernbauer’s key arguments, discusses her theoretical approach and the insights the book offers into (artistic) historiography and global art history methodology.
Keywords: Rezension